The Use of Crossword Puzzle to Improve Students’ Vocabulary at 7th Grade Junior High School of Kendari - Musariana; Yuliyanah Sain; Muflihun; Shufaira Muammar (Universitas Islam Negeri Palopo, 2025)
This study investigates the impact of Crossword Puzzle learning media on junior high school students' English vocabulary knowledge. A quasi-experimental approach was employed, involving 62 students from SMPN 10 Kendari City. The students were divided into experimental and control groups. Pretest and posttest questions were used to collect data, which were analyzed using homogeneity and normality tests, followed by paired-sample t-test. The results showed a significant influence of Crossword Puzzle learning media on improving English vocabulary mastery, concluding that it can be an effective tool for enhancing students' vocabulary skills.